Bipolar Disorder and Diagnostic Course of Asperger Syndrome in an Adolescent: A Case Report - PERDAHLI FİŞ, NEŞE (GALENOS YAYINCILIK, 2010)
Asperger syndrome (AS) is a developmental disorder that is on a diagnostic continuum with autism, and falls under the category of pervasive developmental disorders. Diagnosis may be delayed due to relatively normal speech development, normal intelligence and fair scholar skills, although problems in social development and obsessive, sometimes stereotyped, behavior pattern are recognized from early periods of childhood. Comorbid psychiatric disorders are frequently observed in cases of AS. Sometimes these comorbidities are the initial diagnoses subject to treatment. A detailed family and developmental history of the child is usually helpful for the recognition of the underlying developmental disorder. On the other hand, it is known that the prevalence of bipolar affective disorder in families of individuals with AS is higher than that of the general population, and it is hypothesized that these two disorders might have a common neurobiological basis. In this paper, we aim to discuss an adolescent who first presented with anxiety symptoms at the age of 13 and, with emerging hypomanic symptoms during the course of selective serotonin reuptake inhibitor treatment, which ultimately led to the underlying diagnosis of AS. (Archives of Neuropsychiatry 2010; 47: 360-3)
Keywords: Adolescent; Asperger syndrome; bipolar disorder; diagnosis